Updating energy security and environmental policy: Energy security theories revisited. (1st October 2018) - Proskuryakova, L.
Abstract: The energy security theories are based on the premises of sufficient and reliable supply of fossil fuels at affordable prices in centralized supply systems. Policy-makers and company chief executives develop energy security strategies based on the energy security theories and definitions that dominate in the research and policy discourse. It is therefore of utmost importance that scientists revisit these theories in line with the latest changes in the energy industry: the rapid advancement of renewables and smart grid, decentralization of energy systems, new environmental and climate challenges. The study examines the classic energy security concepts (neorealism, neoliberalism, constructivism and international political economy) and assesses if energy technology changes are taken into consideration. This is done through integrative literature review, comparative analysis, identification of 'international relations' and 'energy' research discourse with the use of big data, and case studies of Germany, China, and Russia. The paper offers suggestions for revision of energy security concepts through integration of future technology considerations. Highlights: The paper examines and revisits the classic energy security concepts. Energy security concepts underlie International Relations debates and policy-making. These concepts do not account for the latest technology changes. These new developments may be identifies through technology foresights.